Reading to learn in a foreign language : an integrated approach to foreign language instruction and assessment - Koda, Keiko, 1954-; Yamashita, Junko, (Professor) (Routledge research in language education, 2019)
"This book describes a theory-guided approach to Foreign Language (FL) course development, implementation, instruction and assessment. It documents the development and implementation of a theory-guided approach designed to exploit cross-linguistically sharable competencies as resources for promoting FL learning. The volume delineates the processes of (a) identifying cross-linguistically sharable competencies, (b) exploring ways of exploiting sharable competencies as resources in promoting language skills through their purposeful use for content learning, (c) implementing the instructional approach in multiple EFL classrooms, and (d) evaluating the approach by comparing learning outcomes across classrooms. It presents a solid conceptual framework that integrates theories in multiple research domains, including second language acquisition, knowledge acquisition, and language assessment. It also provides detailed descriptions of framework construction and classroom implementation - the two processes that are integral to course design and development"--